Disentangling the influence of fishing, demography, and environment on population dynamics of Iberian Peninsula waters fish stocks. (13th December 2019) - Quinzán, M; Castro, J; Massutí, E; Rueda, L; Hidalgo, M
Abstract: Overexploitation and climate change are increasingly causing unanticipated changes in marine ecosystems such as higher variability in fish recruitment or shifts in species dominance and distribution that alter the productivity of fish stocks. This study analyses how external and internal drivers influence population dynamics of hake ( Merluccius merluccius ), white anglerfish ( Lophius piscatorius), four-spot megrim ( Lepidorhombus boscii), and horse mackerel ( Trachurus trachurus) of Iberian Peninsula waters of the Northeast Atlantic across different spatiotemporal scales. Available spawning stock biomass and recruitment have been used as biological data, whereas fishing mortality, demographic data as well as climatic and oceanographic data have been used as drivers. The obtained results indicate that population dynamics of these species are mainly driven by oceanographic variability at regional scale along with fishing pressure and demographic factors, while the impact of large-scale climate indices was minimal. The identified variables represent relevant oceanographic regional processes candidate to be potentially integrated into the stock assessment models and management procedures of these important fishery resources.